(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
In this article, measures to encourage women in our country to engage in entrepreneurship and to provide them with practical help, i.e., support, are widely covered. In addition, the benefits and subsidies provided by our state for women entrepreneurs in order to maintain stability in business and start and develop their entrepreneurship will be discussed.